The Transformative Power of Partnerships Africa Progress Report 2011 - Africa Progress Panel (Switzerland Africa Progress Panel, 2011)
Every Year, the Panel, with support from Secretariat, draws on the expertise of a wide range of institutions and actors to compile a concise overview of the progress Africa has made over the previous year. The report is divided into two sections. The first highlights progress as well as the main obstacles to it in seven areas, namely economic growth, governance, peace and security, social development, food and nutrition security, climate change, and development cooperation and finance. The second section looks at the year ahead and identitifies key trends and obstacles. On that basis, the report provides a series of practical recommendations for policy makers to catalyze action and accelerate much-needed progress
Keywords: Governance, Peace and Security Climate Change Development Finance and Cooperation